A methylation-inspired mesoporous coordination polymer for identification and removal of organic pollutants in aqueous solutions. Issue 3 (25th November 2020) - Chen, Zhonghui; Lv, Ziyu; Lin, Zirong; Chen, Jun; Zhang, Yifang; Wang, Cunli; Qing, Guangyan; Sun, Yifeng; Chi, Zhenguo
Abstract : Tuning the interfacial chemistry of a metal–biomolecule coordination hybrid via bio-inspired methylation for structure enhancement and selective hazard adsorption/identification. Abstract : Qualitative analysis of contamination events and rapid removal of hazardous substances from water are in urgent need for a sustainable environment and human health. Porous coordination polymers (PCPs) bridged by organic ligands through metal nodes in an extendable and periodic manner have emerged as competitive candidates for the detection and removal of hazardous substances. However, the majority of them suffer from high production costs, poor structural stability and environmental problems, which has become a bottleneck for commercial translation. Here, we report a class of phenylalanine-based metal–biomolecule complexes and discuss the impact of subtle sequence variations in modular ligands on their assembly behaviors and structural properties. The phenomenon in which the bioligands dominate the structure formation and surface wettability has been revealed. A Cu(ii )–aspartame coordination polymer, Cu(mDF), with satisfactory chemical stability was selected for removal of organic pollutants in aqueous solution. The mesoporous structure, surface charge and high specific surface area (233.71 m 2 g −1, D mean = 5.65 nm) promote its rapid equilibrium of anionic adsorption within 10 min. In addition, Cu(mDF) possessing an adsorption-induced color-shifting feature provides an ideal platform for organic pollutant detection. Furthermore, Cu(mDF) with biocompatibility and low cost fabrication exhibits antimicrobial properties against C. albicans, E. coli and S. aureus, and may be a potential purifier in wastewater treatment.